Greening of Public Spaces in Cherepovets during Urbanization, 1870 - 1930s: Contradictions of Sustainable Development - Agafonova, Anna B. (European Journal of Sustainable Development, 2020)
From the second half of the XIX century, public gardens and boulevards have become an integral part of provincial Russian towns. They played an aesthetic and sanitary-hygienic role in urban space, being, in fact, green oases in a dusty and noisy town. However, in the XX century, the functional purpose of town gardens has changed: the recreational component is being replaced by the cultural and entertainment one, which became dominant in the Soviet period. This article considers the process of urban space greening in the provincial town of Cherepovets as an example of this process and transforming the functions of the town garden. It also presents the analysis of everyday practices of using urban flora by the population of Cherepovets. The methodological basis of the work is urban environmental history. The research is based on archival and office materials, official statistics, and periodicals. Soviet power kept the tradition of new blocks greening, that formed in the pre-revolutionary period. At the same time, the entertainment and leisure functions of the recreation park supplanted the recreational function, and everyday practices of the town residents showed a dismissive and utilitarian attitude towards the town green spaces. It was due to the peculiarities of urbanization in the city. In the conditions of the constantly expanding town space and the influx of rural population, green spaces could not prevent the degradation of the natural environment, which led to the destabilization of the ecological situation in Cherepovets and prevented the sustainable development of the city. Keywords: urban environmental history, urban greening, a city garden, everyday practice